Anthocyanins from purple corn affect gut microbiota and metabolome in inflammatory bowel disease patients under infliximab infusion: the SiCURA pilot study - Mirco Vacca; Eduardo Maria Sommella; Marina Liso; Giulio Verna; Aurelia Scarano; Annamaria Sila; Margherita Curlo; Mauro Mastronardi; Katia Petroni; Chiara Tonelli; Bruno Di Jeso; Angelo Santino; et al. (Food Science and Human Wellness)
Nowadays, inflammatory bowel disease (IBD)-patient therapies are mainly based on corticosteroid, thiopurine, and immunomodulator treatments. Patients with active disease, that do not respond to corticosteroid and/or thiopurine treatment, can switch to the usage of the chimeric monoclonal antibody infliximab (IFX). However, to date, no treatment appeared to be conclusive in lowering the incidence of IBD relapses. With the aim to increase the effectiveness of IFX treatment, we combined it with an adjuvant purple corn supplementation enriched in anthocyanins. IBD-patients were enrolled before they underwent to the IFX-infusion, and they were allocated in 2 different study arms. Patients in the intervention-arm followed a dietary supplementation with purple corn water-soluble extract, whereas control patients had a daily consumption of red fruit tea. 16S rDNA gene-sequencing and high-resolution mass-spectrometry metabo-lipidomics analyses were conducted on stool and sera samples, respectively. As a result, the experimental intervention mainly affected the serum metabolome of IBD-patients by decreasing the concentration of specific lipids. Focusing on IBD patient annotated taxa, a significant decrease in Lactobacillus and Bifidobacterium relative abundances was found. As far as it concerns the ulcerative colitis patient subset, the experimental intervention led to a decrease in Alistipes and Erysipelotrichaceae UCG-003 genus abundances and a concomitant Parabacteroides increase. On the contrary, after treatment, Crohn’s disease patients did not exhibit metataxonomics differences at the genus level. At the end of the treatment that led to a reshaped microbiota community, the gathered data paves the way for the usage of a specifically designed probiotic supplementation as a valuable strategy for IBD-patients under IFX infusion.